The Data Science Design Manual - Skiena, Steven S. (Texts in Computer Science,, 2017)
This engaging and clearly written textbook/reference provides a must-have introduction to the rapidly emerging interdisciplinary field of data science. It focuses on the principles fundamental to becoming a good data scientist and the key skills needed to build systems for collecting, analyzing, and interpreting data. The Data Science Design Manual is a source of practical insights that highlights what really matters in analyzing data, and provides an intuitive understanding of how these core concepts can be used. The book does not emphasize any particular programming language or suite of data-analysis tools, focusing instead on high-level discussion of important design principles. This easy-to-read text ideally serves the needs of undergraduate and early graduate students embarking on an (3)4z(BIntroduction to Data Science(3)4y (Bcourse. It reveals how this discipline sits at the intersection of statistics, computer science, and machine learning, with a distinct heft and character of its own. Practitioners in these and related fields will find this book perfect for self-study as well. Additional learning tools: Contains (3)4z(BWar Stories,(3)4y (Boffering perspectives on how data science applies in the real world Includes (3)4z(BHomework Problems,(3)4y (Bproviding a wide range of exercises and projects for self-study Provides a complete set of lecture slides and online video lectures at www.data-manual.com Provides (3)4z(BTake-Home Lessons,(3)4y (Bemphasizing the big-picture concepts to learn from each chapter Recommends exciting (3)4z(BKaggle Challenges(3)4y (Bfrom the online platform Kaggle Highlights (3)4z(BFalse Starts,(3)4y (Brevealing the subtle reasons why certain approaches fail Offers examples taken from the data science television show (3)4z(BThe Quant Shop(3)4y ((Bwww.quant-shop.com).